Studies on staphylococcal vaccines for mastitis in dairy cows - H Zafer H; Hüseyin Hadımli; Osman Erganış (Eurasian Journal of Veterinary Sciences)
The aim of the study was to investigate autogenous Staphylococcus aureus vaccines in control of mastitis in dairy cows. Selected strains of S. aureus isolated from both clinical and subclinical cases were used to prepare autogenous S. aureus vaccines (bacterin and bacterin + toxoid) in aluminium hydroxide or mineral oil adjuvants. Sera and milk samples collected from dry cows and heifers were analysed for immunogenic activity of S. aureus vaccines by detection of antibody tilers to staphylococcal antigens, α- and [β-haemolysines. influence on somatic cell counts and ınuamammary S, aureus incidence. Experimental studies were earned out on a total 27 animals (pregnant for 7-8 months 15 dry cows and 12 heifers). Autogenous S aureus vaccines were administered to cows by subcutaneous route in the area of supramammary lymph node or intramuscular route to semitendinous muscle. In comparison with control groups, antibody levels to staphytoccal antigens, and to the α- and (β- haemolisines were significanlty higher (P<0 001, P<0,05 and P<0.05, respectively) in the sera and whey from vaccinated cows. The average somatic cell couni in the milk samples of vaccinated cows were also found to be significantly less (P<0.05) than nonvaccinated cows The ratio for the S. aureus mastitis in a lactating period, in dry cows vaccinated bacterin and combined vaccines was 12,5 % and 8.3 %. respectively, 15.6 % in nonvaccinated dry cows. For the vaccinated heifers, the ratios were 9.3 %, 12.5 %, while 33 3 % in nonvaccinated heifers.